Pelaksanaan Program Kampus Mengajar Angkatan 6 Dalam Mewujudkan Kontribusi Belajar Sambil Berdampak Di SMKS Dharma Bhakti Surabaya - Cantika Al Madinah; Ni Made Ida Pratiwi (Jurnal Pengabdian Kepada Masyarakat, 2023)
The Independent Campus Learning Program (MBKM) is a higher education initiative in Indonesia that involves the concepts of "Freedom to Learn" and "Free Campus" (Independent Campus). MBKM covers several aspects, including the Teaching Campus, which is one of the important elements of this program. One of the target schools for the Class 6 Teaching Campus program is the Dharma Bhakti Surabaya Vocational School (SMK). The Teaching Campus aims to equip students with various expertise and skills by becoming a partner for teachers to innovate in learning, develop creative, innovative and fun learning strategies and models, as well as a form of contribution to learning while providing a positive impact. In this activity, a qualitative descriptive approach was used, with data collection through observation, interviews and documentation. The results of these activities show that the Teaching Campus program at SMKS Dharma Bhakti Surabaya, with a mentoring program to improve numeracy literacy, technology adaptation and administration, is running well and providing benefits for all parties involved, especially in the school environment.